Hubungan Perilaku Orang Tua Dengan Status Gizi Balita Di Desa Bulalo Kabupaten Gorontalo Utara - Maesarah, Maesarah; Djafar, Lisa; Pakaya, Fremly (Gorontalo Journal of Public Health, 2018)
Nutrition is a major factor that has an important role in the growth anddevelopment in the toddlers. In the nutritional fulfillment of the toddler,the mother plays very important role. This study aimed to determinethe factors associated with the behavior of parents with the nutritionalstatus of toddlers. The research design was used analytical surveywith cross sectional study approach. The population in this researchwas 213 Balita, the sample in this research was 136 children in BulaloVillage Kwandang District, North Gorontalo District, the samplingmethod was used purposive sampling technique. Data collection ofrespondents in general using questionnaires, data analysis usingSPSS program version 21.0. Bivariate analysis to know the existenceof relation between dependent variable and independet by using chisquared test α = 0,05. The results showed that there was a correlationbetween parents' knowledge on the Nutritional Status of Toddlers (p =0,000), there was a correlation between parental attitudes with thenutritional status in the toddler (p = 0,000), there was a correlationbetween parental action with the nutritional status in the toddler (p =0,000 ). This study recommends to parents to always pay attention tothe type of food consumed and the mothers should often follow thecounseling done by midwives and nutrition officials so that thenutritional status of toddlers has increased.